(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses the issues of developing telecommunication services, analyzes the experience of their creation and implementation. Issues related to the development and operation of this kind of services were the basis for determining the topics of many qualifying works (master’s theses, diplomas) completed by graduates of Osh TU in the laboratory of Cybernetics and Information Technologies of the Faculty (KiIT) of Osh TU. The article analyzes the results obtained, provides examples of qualifying work and promising areas for research.